Risk of pneumonitis in cancer patients treated with immune checkpoint inhibitors: a meta-analysis - Abdel-Rahman, Omar (Ther Adv Respir Dis, 2016)
BACKGROUND: A meta-analysis of the risk of pneumonitis associated with the use of immune checkpoint inhibitors in cancer patients has been conducted. METHODS: Eligible publications included randomized trials of cancer patients on immune checkpoint inhibitors, describing events of all-grade and high-grade pneumonitis. RESULTS: After exclusion of noneligible citations, a total of 11 clinical trials were eligible for the meta-analysis. The odds ratio was 3.96 [95% confidence interval (CI): 2.02–7.79; p < 0.0001] for all-grade pneumonitis and 2.87 (95% CI: 0.90–9.20; p = 0.08) for high-grade pneumonitis. Moreover, the odds ratio of all-grade pneumonitis with a nivolumab/ipilimumab combination versus ipilimumab monotherapy was 3.68 (95% CI: 1.59–8.50; p = 0.002) and, for high-grade pneumonitis, it was 1.86(95% CI: 0.36–9.53; p = 0.46). Subgroup analysis did not reveal a difference between lung cancer patients and other cancer patients in the risk of pneumonitis. CONCLUSIONS: Our analysis provided evidence that the use of immune checkpoint inhibitors is associated with an increased risk of all-grade pneumonitis compared with chemotherapy or placebo controls.